Improving The Ability of E-Business-Based Business Management in The Entrepreneurial Community - Hartini; Richy Wijaya; Husna Leila Yusran; Wegig Murwonugroho; Teddy Siswanto; Ahmad Buchori (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The Cordova Bina Amanah Entrepreneurial Group is an institution that provides lessons and entrepreneurship skills which is held annually without charging any fees to the participants. Partner problems that are prioritized to be resolved during the implementation of the Community Service Program are difficulties in marketing the products produced, lack of knowledge in financial management and limited ability in business management during the pandemic. Solutions that can be offered to solve partner problems are by providing counseling, training, and assistance in managing marketing, finance and application implementation with the output target in the form of a guidebook and the Trisakti Online Shop (TOS) application. The implementation of the activity is carried out using the Extension and Training method to convey all the materials needed and followed by mentoring so that participants can apply the material that has been obtained appropriately. The activities will be divided into 5 stages, namely the preparation stage, the implementation stage, the mentoring stage, evaluation, and the independent and sustainable stage. The results of the training show that there is an increase in knowledge by partners based on tests carried out before and after the training.